(untitled) (Proximus Journal of Sports Science and Physical Education, 2025)
The research problem crystallized around the fact that some children lack the ability to focus their attention when performing the skill of shooting from a fixed position with a handball. This is due to a lack of sufficient attention to motor education lessons and the preoccupation of most children with modern technology. This prompted the researcher to study this important aspect and work to improve and develop it by using minigames that stimulate children’s attention and engage them during play. The researcher developed an educational program containing mini-games and implemented it on a sample of kindergarten children aged 4- 6 years. The program included a set of mini-games in addition to educational guidance. The goal was to develop focus. The researcher used the experimental method with a single-group design and conducted a pretest for the research sample over a period of two months, with three units per week. The tests were then conducted. The post-test and with the same procedures followed in the pre-tests to identify the extent of the impact of the educational program prepared with mini-games on the concentration of attention and the skill of shooting from a standstill with a handball for children aged 4-6 years. After processing the data using appropriate statistical methods, the results showed the effectiveness of using the prepared curriculum to develop the concentration of attention and the skill of shooting from a standstill with a handball for kindergarten children aged (4-6) years. In light of the conclusions we reached, the following recommendations were raised: the necessity of using an educational curriculum with mini-games within the kindergarten curriculum and the necessity of preparing the educational environment with the necessary capabilities and tools to implement the games and prepare educational recreational games for the various sports activities in which children show weakness in practice for the purpose of developing and improving the concentration of attention and the skill of shooting from a standstill with a handball and to enhance self-confidence